Investigation of an integrated hydrogen production system based on nuclear and renewable energy sources: Comparative evaluation of hydrogen production options with a regenerative fuel cell system - Orhan, Mehmet Fatih (2015)
Hydrogen has risen as a sustainable and efficient energy carrier option in reducing environmental pollution, and is seen as a potential solution for the current energy crisis. Hydrogen production via water decomposition is a potential process for direct utilization of nuclear thermal energy to increase efficiency and thereby facilitate energy savings. While many of the available renewable energy resources are limited due to their reliability, quality, quantity and density, nuclear energy has the potential to contribute a significant share of energy supply with very limited impacts to climate change. The proposed model in this study is an integrated hydrogen production system combining both nuclear and solar energy sources. This integrated system includes storage of hydrogen and its conversion to electricity by a regenerative fuel cell system when needed. There are many matured water splitting processes that can be linked with the nuclear and solar energy sources to decompose water to its constituents, among which is hydrogen. In this regard, a comparative study is carried out to evaluate an optimal and feasible hydrogen production/storage process with a regenerative fuel cell that can be linked to this integrated system. Studies conducted here on hydrogen production processes show the thermochemical water decomposition to be the better option for producing hydrogen, comparing to electrolysis, due to its high efficiencies and low costs. Energy and exergy efficiencies of various hydrogen production processes, and fuel cell systems are evaluated and compared. Also, a parametric study is conducted on these efficiencies to see the effect of various operating conditions.